Financial Inclusion in Muslim-Majority Countries: Overcoming Economic and Social Challenges Through Islamic Lending - Ahmed Hassan, Ramzi Abdullah (Invest Journal of Sharia & Economic Law, 2024)
This study explores the impact of Islamic loans on promoting financial inclusion and addressing socio-economic issues in Muslim-majority countries.   It compares Islamic loans with other financial instruments to demonstrate their contribution to creating an inclusive financial system.The research analyzes the challenges associated with using Islamic loans to enhance financial inclusiveness and mitigate economic and social challenges. The research explores the unique characteristics of Islamic loans and their impact on financial accessibility, savings, credit availability, and comprehensive banking services through a comparative descriptive methodology, including a literature review and data analysis. The study's findings reveal that Islamic finance presents opportunities for financial inclusion. However, there are several obstacles that need to be addressed, including regulatory and legal frameworks, scalability issues, global integration, public awareness, and technical accessibility. To promote the adoption of Islamic finance and advance financial inclusion, collaboration among regulatory bodies, financial institutions, legislators, and the public is crucial. Further research and the development of effective strategies are necessary to promote financial inclusion in the Islamic economy.